Isolated soft tissue tuberculosis: a case report and literature review - Chen, Baolin; Bao, Yuxiang; Chen, Jun; Zhang, Yunpu; Wen, Qifu; Wang, Kai; Cheng, Xiaoming; Lv, Junyuan (Frontiers in Medicine, 2023)
Soft tissue tuberculosis is a rare extrapulmonary form of tuberculosis with limited experience in diagnosis and treatment. Soft tissue tuberculosis is an extrapulmonary infection with atypical clinical symptoms that can be easily misdiagnosed. In this article, we report a case of a female patient with isolated soft tissue tuberculosis who presented with a progressively enlarging subcutaneous mass as the primary symptom, and was suspected of having a subcutaneous lipoma after ultrasonography. A review of the literature revealed that soft tissue tuberculosis is insidious and mainly occurs in muscles and subcutaneous tissues. It was indicated by histopathology and qPCR testing for Mycobacterium tuberculosis complex. There is no standard treatment protocol for soft tissue tuberculosis, and a comprehensive regimen of surgical debridement of the lesion combined with chemotherapy can be used following the guidelines for treating extrapulmonary tuberculosis.Early diagnosis and standardized anti-tuberculosis treatment can significantly improve the prognosis of patients.